Produksi Pupuk Cair dari Isolat Bakteri Limbah Sayur Pasar Angso Duo Jambi dalam Meningkatkan Perekonomian dan Kesehatan Lingkungan Masyarakat Jambi - Harlis, Harlis; Budiarti, Retni S; Kapli, Hari; Sanjaya, M Erick (Universitas Jambi, 2019)
Angso Duo Market is the largest traditional market in the city of Jambi, with an area of ​​± 5 Ha. The amount of waste produced by Angso Duo market every day is around 105 tons per day with a ratio of 70% biodegradable waste, 25% recycled (organic and paper) and 5% other waste. Of the 75% of waste that is around 60% is waste in the form of vegetables, most of which are mustard and cabbage. Vegetable waste has great potential to be used as organic fertilizer because it has good and complex nutrients such as protein, fat carbohydrates, calcium, phosphorus, iron, vitamins A, B and C, folic acid, fiber, water and sodium. The advantage of liquid organic fertilizer is that it contains enough nitrogen as a constituent of plant protein and chlorophyll. The results showed 6 types of bacteria namely Planococus, Neisseria, Halobacter, Azomonas, Azotobacter and Bruccella which were formulated into liquid fertilizers with a basic substrate of vegetable cabbage and mustard waste.Then tested the ability of bacteria to dissolve nitrogen, phosphorus and potassium as potential bacteria as liquid fertilizer